Application of media notion to improve students' critical thinking through TaRl learning at SMAN 6 Malang - Rahmatulloh, Fawaz Sani; Purwanto, Purwanto; Ulfi, Takhiyatul; Oraby, Ghada Abd Elsattar Mohammed (Jurnal teori dan praksis pembelajaran IPS (Online), 2023)
This research was motivated by the low critical thinking ability of students in Geography subjects at SMA Negeri 6 Malang. This study aims to improve students' critical thinking skills by using a project-based learning model based on TaRl learning strategies. This type of research is classroom action research. The subjects of this study were students of grade X-I SMA Negeri 6 Malang. The instruments used in this study were interview sheets, observations, test questions, and documentation. Data collection techniques consist of interviews, observations, tests and documentation. Data analysis in this study used quantitative and qualitative data analysis. The result of this study is to improve students' thinking processes with a problem-based learning model based on Tarl learning strategies assisted by media notion in class X-I SMA Negeri 6 Malang. This is shown from the results of the analysis of each cycle showing a significant improvement so that students' thinking processes can develop.